Agglomeration effect on subsidiary capability scope and performance: an empirical study of electronic industry in China. (2017) - Li, Peng-Yu; Lo, Fang-Yi
This paper examined the factors that influenced subsidiaries' capabilities and performance. The influence of host country factors, especially sub-national factors, on subsidiary capability scope and development have not been examined extensively in previous studies. In this study, we explore the impact of the two agglomeration effects on subsidiary capability scope and performance. Agglomeration of foreign firms brings the advantage of specification and on the other hand agglomeration of state-owned enterprises (SOEs) brings connection development those negatively affect subsidiary capability scope but positively affects subsidiary performance. Our data comes from Taiwanese subsidiaries of electronics industry invested in China between 2003 and 2007. The results show the agglomeration effects of foreign firms and SOEs leads subsidiaries to develop less capability scopes because of specialisation and limited local resources, however, agglomeration effect contributes to subsidiary performance.